RESEARCH AND MODELING OF THE FINISHING METHOD OF CYLINDRICAL GEAR TEETH THROUGH COLD PLASTIC CALIBRATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The operational performance of gearwheels is largely determined by the accuracy of the parameters and the quality of the working surfaces of the teeth, the requirements for which are constantly increasing. To optimize the machining conditions (increasing productivity, tool durability and the quality of the machined gearwheels), a method for finishing machining by calibration on gear-shaving and thread-rolling machines is proposed in the work. Experimental studies have been conducted to prove the operability of the proposed method. The results obtained have been analyzed and compared with gear-milled gearwheels in terms of kinematic accuracy, smoothness of operation and contact of the teeth. Regression models have been obtained for the accuracy parameters of the teeth before and after processing by calibration and subsequent heat treatment, the analysis of which shows that their size is largely determined by their input values. The results of the studies confirm the assumption of the presence of a correlation between the same accuracy parameters at the input and at the output during processing by calibration and subsequent heat treatment.